SCREEN TIME AND DIETARY QUALITY AMONG NURSING STUDENTS AT THE COLLEGE OF NURSING (FEMALE), BADIN (Journal of Medical & Health Sciences Review, 2025)
Introduction: Increased screen time is a common trend among nursing students due to academic and social demands. However, its influence on dietary quality remains unclear and understudied. Objective: This study aimed to assess the association between screen time and dietary quality among nursing students.Methods: A descriptive cross-sectional study was conducted among 140 nursing students. Data were collected through a self-administered questionnaire using Google Forms. The College of Nursing, Female, Badin, was selected as the research design. Data analysis was performed by using Fisher’s Exact Test to examine the association between screen time and dietary quality.Results: Most participants reported high screen time and moderate dietary quality. However, Fisher’s Exact Test indicated no statistically significant association between screen time and dietary quality (p = 0.282).Conclusion: The results revealed no statistically significant relationship between the two variables. Although high screen time and moderate dietary quality were common among participants, the lack of a significant association suggests that screen time alone may not be a primary factor influencing dietary habits in this population.